The role and therapeutic potential of SIRTs in sepsis - You, Jiaqi; Li, Yilin; Chong, Wei (Frontiers in Immunology, 2024)
Sepsis is a life-threatening organ dysfunction caused by the host's dysfunctional response to infection. Abnormal activation of the immune system and disturbance of energy metabolism play a key role in the development of sepsis. In recent years, the Sirtuins (SIRTs) family has been found to play an important role in the pathogenesis of sepsis. SIRTs, as a class of histone deacetylases (HDACs), are widely involved in cellular inflammation regulation, energy metabolism and oxidative stress. The effects of SIRTs on immune cells are mainly reflected in the regulation of inflammatory pathways. This regulation helps balance the inflammatory response and may lessen cell damage and organ dysfunction in sepsis. In terms of energy metabolism, SIRTs can play a role in immunophenotypic transformation by regulating cell metabolism, improve mitochondrial function, increase energy production, and maintain cell energy balance. SIRTs also regulate the production of reactive oxygen species (ROS), protecting cells from oxidative stress damage by activating antioxidant defense pathways and maintaining a balance between oxidants and reducing agents. Current studies have shown that several potential drugs, such as Resveratrol and melatonin, can enhance the activity of SIRT. It can help to reduce inflammatory response, improve energy metabolism and reduce oxidative stress, showing potential clinical application prospects for the treatment of sepsis. This review focuses on the regulation of SIRT on inflammatory response, energy metabolism and oxidative stress of immune cells, as well as its important influence on multiple organ dysfunction in sepsis, and discusses and summarizes the effects of related drugs and compounds on reducing multiple organ damage in sepsis through the pathway involving SIRTs.SIRTs may become a new target for the treatment of sepsis and its resulting organ dysfunction, providing new ideas and possibilities for the treatment of this lifethreatening disease.